Arthropod and Earthworm Populations on Irrigated Rice Farming Land after Paraquat Herbicide Application - Edhi Martono; Ruwinda Wahyu Wijayanti; Kusnanik Kusnanik; Diprilla Vega Torani (Universitas Gadjah Mada, 2021)
Paraquat dichloride is a herbicide compound commonly used to control grasses and broadleaf weeds. Its use is presently under scrutiny as there is a report that this herbicide is very harmful and hazardous to the environment, especially to wild fauna surrounding farming sites. An irrigated rice farming locale experiment was conducted to observe the effect of paraquat treatment on rice plant biotic environment, particularly its arthropods and earthworm population, two of the most prominent fauna easily affected by paraquat. The study was carried out in Seyegan District, Sleman Regency, Special Region of Yogyakarta Province, on irrigated rice land from October 2018 to February 2019. Four treatments of paraquat, i.e. control (0 kg/ha paraquat), lower dose (0.8 kg/ha), medium dose (1.6 kg/ha), and higher dose (3.2 kg/ha) were arranged. Carbendazim 5 kg/ha was also applied as comparing pesticides, especially for paraquat’s effect on the earthworm. The treatments were replicated five times in a plot of 5 x 5 m2. The number of arthropods and earthworms was observed in about two weeks intervals or more. The observation was done for the number of arthropods and their families, while for earthworms, only for their numbers. The arthropods population data were subjected to diversity indices and statistical analysis, while the earthworms data were statistically analyzed. The result showed that the arthropod numbers in treated plots were statistically significantly different, but biologically their number was still abundant. Their diversity did not differ from the control treatment at all. The arthropod numbers were 2007, 1483, 1095, 1746, and 1204 in control, lower, medium, higher, and carbendazim plots. The earthworms' numbers were still plenty; those in the higher dosage did not differ significantly from those in control. Their numbers from control, lower, medium, higher dose, and carbendazim plots were 811, 658, 567, 882, and 445 individual earthworms.